Segetoside I, a plant-derived bisdesmosidic saponin, induces apoptosis in human hepatoma cells in vitro and inhibits tumor growth in vivo. (August 2016) - Firempong, Caleb Kesse; Zhang, Hui Yun; Wang, Yan; Chen, Jingjing; Cao, Xia; Deng, Wenwen; Zhou, Jie; Wang, Qiang; Tong, Shan-Shan; Yu, Jiangnan; Xu, Ximing
Graphical abstract: Abstract: Segetoside I is a plant-derived bisdesmosidic saponin from Vaccaria segetalis (Neck) with reported anticancer activities. This development has raised an interest in the therapeutic potential of segetoside I. Here, we report the in vitro and in vivo antitumor activities of segetoside I against some selected cancer cell lines (HepG2, human hepatoma; H22, mouse hepatoma; MCF-7, breast cancer; U251, gliocoma; BGC, HGC & SGC, gastric cancinoma; Lovo-1, colon cancer). MTT bioassay analysis showed that HepG2 cells were the most sensitive to segetoside I compared with other cancer cell lines, with lower toxicity in healthy mouse embryonic fibroblast cells. Segetoside I pretreatment of HepG2 resulted in apoptotic induction, dose-dependent DNA fragmentation, inhibition of cell migration, up-regulation of Bax and down-regulation of Bcl-2, which indicated that an apoptotic signaling event could have been initiated. The segetoside I also suppressed hepato-tumour growth in mice with virtually no cytotoxicity and prolonged animal survival, making it a strong oncology drug agent. These findings showed that segetoside I exhibited its antitumor activity via apoptotic induction and significantly support the possible application of the antitumor agent as a potential chemotherapeutic candidate worthy of further investigations.